Ethnography on dental pain in pijao population in Ortega, Tolima - Ospina-Lozano, Edson Jair; Liscano-Pinzón, Yesica Daniela (Revista Facultad de Odontología Universidad de Antioquia, 2021)
Introduction: from a biological perspective, dental pain is a symptom that indicates damage to the dental pulp. Nevertheless, from a human-centered perspective, it is considered a process where substantial elements of the health culture are expressed, in this case, the symbolic representations about the mouth and teeth, and the different strategies that the population uses to solve this ailment. The objective was to understand the way in which the Pijao population understands and cares about their dental pain. Method: ethnographic study. Use of tools such as documentary analysis, participant observation, semi-structured interviews and field diary. Results: this kind of pain is common in the population, and is related to the presence of dental caries, and indicates the appearance of dental loss. Furthermore, the way in which it is understood and cared for is related to the symbolic representations about the mouth and teeth, and about their diseases and their care. Its initial treatment is given to the family through herbal and pharmaceutical resources. Considering its intensity, people turn to dental care for its therapeutic efficacy. This is the main reason to visit the dentist. Conclusions: dental pain is a process where subjects establish an awareness of their body. Likewise, it indicates poor oral health conditions, difficulties in the implementation of policies for Primary Oral Health Care, and the existence of economic and cultural barriers to access to health institutions.